Law as a Tool for Decolonizing Knowledge: A Critical Study of the Legal Education Curriculum in Indonesia - Shodiq, Md (Ipso Jure, 2025)
The legal education system in Indonesia is still trapped in a colonial epistemological structure that inherits the legalistic and positivistic mindset of the Dutch legal system. The dominant curriculum model places law as a tool of state power and ignores the diversity of local legal systems, such as customary law, Islamic law, and community practices. This epistemic inequality results in a distance between the legal theory taught and the legal reality experienced by society. Through a normative juridical approach, this study analyzes Law Number 20 of 2003 concerning the National Education System (UU Sisdiknas) as a legal basis for efforts to decolonize the legal curriculum. Article 3 and Article 38 paragraph (2) of the National Education System Law provide normative legitimacy for the integration of local values, legal plurality, and interdisciplinary approaches in legal education. The decolonization of legal knowledge should encourage a change in the curriculum from technocratic to emancipatory one, by emphasizing social justice, community participation, and the critical awareness of law students. Legal education needs to present law as an instrument of social transformation, not just a procedural norm. By adopting progressive legal thinking and Southern epistemology, Indonesian legal education can contribute to a more democratic, inclusive, and equitable legal system. Curriculum reform is a strategic agenda to dismantle colonial hegemony and build legal awareness that is contextual and on the side of the people.